ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECELAKAAN KERJA PADA PEKERJA MAINTENANCE ELEKTRIKAL DALAM MENERAPKAN WORK PERMIT DI PT. X SEMARANG - Wirdati, Ismi Elya; Denny, Hanifa Maher; Kurniawan, Bina (Jurnal Kesehatan Masyarakat (e-Journal), 2015)
occupational accidents are unexpected events that can occur in the workplace, to the place of work and from the workplace. Factors causes of accidents include human, equipment, environment. Accidents are contained in PT. X Semarang occur in electrical maintenance workers. Because the electrical workers are high hazard. So the company applying for a work permit control. This research to determine factors that influence incidence of workplace accidents in electrical maintenance workers in applying work permit. The researchers took factors of knowledge, compliance, PPE use and dissemination work permit. Qualitative research design used cross sectional. The sampling method by total sampling that all electrical maintenance worker. Technique of data collection such as in-depth interviews, documentation and observation. Reliability and validity of the data with source triangulation and triangulation technique. Based on the results of worker factors that caused workplace accidents that implementing SOP compliance work permit, the use of PPE and socialization work permit